2017
DOI: 10.1186/s13033-017-0151-5
|View full text |Cite
|
Sign up to set email alerts
|

Help seeking and suicidality among people with epilepsy in a rural low income country setting: cross-sectional survey

Abstract: BackgroundsEpilepsy is a serious neurological disorder associated with a high level of psychiatric comorbidity. Suicidality is a recognised complication of epilepsy. As part of developing an integrated service for people with epilepsy (PWE) and priority psychiatric disorders within primary care, a cross-sectional study was conducted in a rural district in Ethiopia to investigate patterns of help-seeking, suicidality and the association with duration of untreated epilepsy (DUE) among PWE.MethodsCases were ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 43 publications
4
18
1
Order By: Relevance
“…9 It is also lower than in a study conducted in low-income countries in which about 80% of respondents did not seek any treatment. 21 In the current study, 41.7% of participants did not seek help from modern health institutions; this result is supported by a study conducted from Nigeria in which 55.8% of participants did not take epileptic patients to a hospital during a seizure. 22 This may be a result of cultural influences regarding the causes of and treatment options for seizure, as people in many developing countries believe that epilepsy cannot be cured by modern treatment, but rather by traditional treatments.…”
Section: Discussionsupporting
confidence: 74%
“…9 It is also lower than in a study conducted in low-income countries in which about 80% of respondents did not seek any treatment. 21 In the current study, 41.7% of participants did not seek help from modern health institutions; this result is supported by a study conducted from Nigeria in which 55.8% of participants did not take epileptic patients to a hospital during a seizure. 22 This may be a result of cultural influences regarding the causes of and treatment options for seizure, as people in many developing countries believe that epilepsy cannot be cured by modern treatment, but rather by traditional treatments.…”
Section: Discussionsupporting
confidence: 74%
“…Tsigebrhan et al found that poorer patients were susceptible to depression, and their economic level was associated with suicidal behavior in a rural low-income country. 27 The annual income of the OR P 95% CI The bold values are statistically significant (P<0.05).…”
Section: Discussionmentioning
confidence: 99%
“…A study in Malawi among people with epilepsy indicated that they sought both traditional and modern medicine to treat their condition [13]. Other countries in Africa face this multiplicity of health providers like in Ghana [14] South Africa [15] and Ethiopia [16,17]. It has been noted that biomedical treatment offered at health facilities is not adequate.…”
Section: Discussionmentioning
confidence: 99%